The effects of active commuting on cardiovascular disease incidence and mortality - a literature review - Pędras, Marek; Perenc, Helena; Majka, Karolina; Krawczyk, Kornelia; Pasieka, Karolina; Kosar, Michał; Kupniewski, Kuba; Korzonek, Urszula; Kosiorowska, Paulina (Quality in Sport, 2024)
Objective: Cardiovascular disease (CVD) remains a leading cause of death in developed countries, with physical inactivity identified as a major risk factor. Despite widespread promotion of physical activity by health organizations and general awareness of its benefits, inactivity is increasing. Active commuting, such as walking or cycling to replace driving or public transport, offers a practical way to integrate physical activity into daily routines without requiring additional time. This study aims to evaluate the impact of active commuting on reducing CVD incidence and mortality, considering the duration and mode of commuting. Methods: An extensive literature review was conducted using PubMed, focusing on studies from 2000 to 2023. Results: The review revealed mixed findings on the effects of active commuting on cardiovascular health. Studies such as Celis-Morales et al., indicated significant reductions in CVD incidence and mortality with longer durations of walking and cycling. Conversely, studies like Barengo et al. and Lopirinzi et al. reported no significant benefits from active commuting alone. Differences in study design, population demographics, and measurement methods likely contribute to these inconsistencies. Conclusions: Overall, evidence suggests that while active commuting, particularly cycling, can reduce CVD risk, its benefits are influenced by the intensity and duration of activity and individual fitness levels. Active commuting may be most effective when combined with other forms of physical activity. The review highlights the need for more standardized research to accurately quantify the health benefits of active commuting and inform policy development.